2018
DOI: 10.7759/cureus.3263
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pseudo-pneumothorax with Complications

Abstract: Pseudo-pneumothorax occurs after inappropriately diagnosing a pneumothorax based on a chest X-ray. This can be attributed to skin folds, bed sheets, previous pneumothorax, heating blankets, clothes, and other circumstances that may mimic the radiographic findings of a pneumothorax. We present a case where a patient underwent a tube thoracostomy due to the diagnosis of a pneumothorax that was not, in fact, present. The unnecessary intervention was complicated by hemoptysis and cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Distinguishing between pneumothorax and pseudo-pneumothorax is critical, as unnecessary interventions can lead to serious complications. Niazi et al reported a case of a patient with pseudo-pneumothorax due to a skin fold that was misdiagnosed as pneumothorax and therefore underwent a tube thoracostomy, which led to vascular injury and cardiac arrest [10]. Other possible tube thoracostomy complications include nerve damage, fistula formation, infections, and organ perforations [11].…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing between pneumothorax and pseudo-pneumothorax is critical, as unnecessary interventions can lead to serious complications. Niazi et al reported a case of a patient with pseudo-pneumothorax due to a skin fold that was misdiagnosed as pneumothorax and therefore underwent a tube thoracostomy, which led to vascular injury and cardiac arrest [10]. Other possible tube thoracostomy complications include nerve damage, fistula formation, infections, and organ perforations [11].…”
Section: Discussionmentioning
confidence: 99%
“…The curved shadow of skin folds can mimic the visceral pleural margin and can often be misinterpreted as a pneumothorax leading to unnecessary interventions. 1 The area lateral to this sharp margin can often be perceived darker than the lung medial to it. 2 Optical illusions like Mach band effect are often helpful in demarcating the boundaries of anatomic structures with different optical densities on radiographs.…”
Section: Commentmentioning
confidence: 99%